Effects of PECS on the Emergence of Vocal Mands and the Reduction of Aggressive Behavior Across Settings for a Child With Autism. (August 2019) - Hu, Xiaoyi; Lee, Gabrielle
Effective strategies to address communication and behavior challenges are critical in early intervention programs. The purpose of this study was to investigate the effects of the Picture Exchange Communication System (PECS) on vocal mands and aggressive behavior displayed by a child with autism in China. One 4-year-old boy with autism participated in this study. The experimental design was a multiple baseline across three settings. The PECS intervention involved the first three phases described in the PECS manual. The results indicated that PECS effectively increased vocal mands and decreased aggressive behavior maintained by access to preferred items in all three settings. The results also suggested that vocal mands were potentially controlled by pictures in the PECS book. One week following the completion of the intervention, the child maintained the PECS exchanges at a high level with increased vocal mands. His aggressive behavior remained at almost zero occurrences. Results of this study have important implications to early intervention educators working with children with autism.